Nurses' Attitude Toward End of Life Care in Emergency Departement and Intensive Care Unit In Rural Hospital - Muhamad Zulfatul A'la; Zumrotul Farikhah; Mulia Hakam (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: Death is a psychological and physical event that affects patients caring for, especially in Emergency Departement (ED) and the Intensive Care Unit (ICU). Patients and families need the end of life care from a health professional, including nurses. Nurses need to have knowledge, skill, attitude, and interpersonal competencies to provide end of life care. Objective: This study aimed to explored differences of attitudes towards dying care between ED and ICU ward nurses in a rural hospital.Method: Variable in this study was the nurse's attitude. This study used a quantitative comparative cross-sectional research design. The samples were 24 nurses from the emergency ward and 16 from the intensive care unit who were recruited by total sampling. Data were collected to use Frommelt Attitudes Towards the Care of the Dying Care Form B Indonesian version (FATCOD-BI).Result: The results revealed that nurses' attitudes toward caring for dying patients in the ED were 101.42±6.646 (30-150) on average, and in the intensive care unit was 106.44±7.633 (30-150) on average. Nurses in the ICU had a more positive attitude than the ED (p = 0.034). There are differences between the proportion of respondents based on gender, level of education, length of time working in the emergency ward, and ICU. The result showed gender, level of education, and range of time working could influence nurses' attitudes towards caring for dying patients in the emergency ward and ICU.Conclusion: There is a difference between nurses' attitudes towards EOLC in the ED and ICU room at rural hospitals. Moreover, the ICU nurses have a more positive attitude than ED nurses.